Pengaruh Aplikasi Gel Nanas (Ananas comosus) Terhadap Kekerasan Email Gigi - Sistianingsih, Sistianingsih; Setyadi, Ariosta; Purnomo, Brigitta Natania Renata; Prihatiningsih, Tyas (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2022)
Tooth discoloration is one of the aesthetic problems that have a significant impact on psychological conditions. Pineapple is a natural ingredient that can be used as an alternative to dental bleaching. Citric acid and malic acid in pineapple can bind calcium in teeth and cause porosity of enamel crystals which in turn reduces the enamel hardness. The aim of this study is to determine the effect of pineapple gel (Ananas comosus) application on tooth enamel hardness. The study design was a pretest and post-test controlled group design. Twenty five post extraction maxillary premolars were divided into 5 groups. The pH test of pineapple gel was done before treatment, each group was applied pineapple gel 25%, 50%, 75%, 35% hydrogen peroxide gel, and gel without active compounds. The hardness test was carried out using Vickers Hardness Tester. Data analysis used Paired t-test, Wilcoxon, Kruskal Wallis, one way ANOVA using probability 0,05. Paired t-test results showed significant differences in tooth enamel hardness before and after application of pineapple gel 50% (0,04), 75% (0,00), 35% hydrogen peroxide gel (0,04), but no significant difference in tooth enamel hardness before and after application of 25% pineapple gel (0,16). Wilcoxon test results no significant difference in tooth enamel hardness before and after application of gel without active compounds (0,08). Kruskal Wallis (0,17) and one way ANOVA (0,06) test results no significant differences in tooth enamel hardness between groups. The results of this study concluded that pineapple gel application can be recommended as an alternative to dental bleaching.